DAMPAK KEBIJAKAN PERDAGANGAN GULA TERHADAP PROFITABILITAS USAHA TANI TEBU: KASUS DI KABUPATEN KLATEN JAWA TENGAH - Tjetjep Nurasa; Iwan Setiajie A. (Buletin Ilmiah Litbang Perdagangan, 2008)
Trade policy does not only affecting the sugar cane at macro level, but also in micro level through the price mechanism of output change. The prices increases in 3 scenarios, that are the suger price at producer price from IDR 3,410 to IDR 1,461,3 for the A scenario, to IDR 2,600 for the B scenario, to IDR 2,270 for C scenario. The adantage of sugar cane farming in district of Klaten, Central Java in planning smaller than keprasan. This isdue to the expensive of preparation of crop, seed and plant, where as in keprasan doess not need it, Even, the advantages of earty harvest in non irrigation area in Klaten district decreased sharply. All policyes scenarios causes advantage of natura sugar cane in degradation sharply in which those scenarios cause advantages tend to negative. It means non profit nor in rice field either in non irrigated. While the crop of ratoon (keprasan), the profit decrease but non negative. This means that the farmer sugar cane will poor extremally if they are in protection tariff. Abolition policy of tariff or non-tariff is also will cause decreases profits. Therefore, the combination policy of tariff and non-tariff is still needed in order to protect farmer of sugar cane and national sugar industry.